2014
DOI: 10.1002/ajhb.22551
|View full text |Cite
|
Sign up to set email alerts
|

Stunting, adiposity, and the individual‐level “dual burden” among urban lowland and rural highland peruvian children

Abstract: BackgroundThe causes of the “dual burden” of stunting and obesity remain unclear, and its existence at the individual level varies between populations. We investigate whether the individual dual burden differentially affects low socioeconomic status Peruvian children from contrasting environments (urban lowlands and rural highlands), and whether tibia length can discount the possible autocorrelation between adiposity proxies and height due to height measurement error.MethodsStature, tibia length, weight, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 87 publications
2
29
0
1
Order By: Relevance
“…Although our study does not indicate an increased overall risk of higher BMIZ, we did find differences between urban and rural children at ages 5 and 8 y, and between indigenous and nonindigenous children at age 8 y. RRs of prevalent and incident BMIZ > 1 for rural and indigenous children were >1, but not significantly. Another study in Peru found that in urban lowland children, length was positively associated with BMI (37), which is consistent with our finding that infant stunting is associated with reduced prevalence and incidence of BMIZ > 1 at age 8 y in urban children. The authors of that study suggested that differences between rural and urban populations may arise from environments that present different opportunities for catch-up growth and the accrual of adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Although our study does not indicate an increased overall risk of higher BMIZ, we did find differences between urban and rural children at ages 5 and 8 y, and between indigenous and nonindigenous children at age 8 y. RRs of prevalent and incident BMIZ > 1 for rural and indigenous children were >1, but not significantly. Another study in Peru found that in urban lowland children, length was positively associated with BMI (37), which is consistent with our finding that infant stunting is associated with reduced prevalence and incidence of BMIZ > 1 at age 8 y in urban children. The authors of that study suggested that differences between rural and urban populations may arise from environments that present different opportunities for catch-up growth and the accrual of adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
“…However, other stressors such as increased radiation, aridity, broader temperature ranges, and poorer diets may also affect developmental characteristics in these environments (Leonard 1989;West et al 2007;Pomeroy et al 2014). Evidence for HA adaptation was shown in Tibetans (Beall et al 2010;Bigham et al 2010;Yi et al 2010;Peng et al 2011;Simonson et al 2012), Andeans Bigham et al 2009Bigham et al , 2010Zhou et al 2013;Eichstaedt et al 2014), and Ethiopians (Alkorta-Aranburu et al 2012;Scheinfeldt et al 2012;Huerta-Sanchez et al 2013;Udpa et al 2014), thus demonstrating the effects of long-term exposure to hypoxia above 3000 m. However, little is known about the effects of moderate levels of hypoxia on human physiology, such as those found at intermediate altitudes (IA), which we define hereafter as altitudes between 2000 and 3000 m. Some indication that moderate hypoxia may have a physiological impact comes from evidence of an albeit modest occurrence of Acute Mountain Sickness (AMS), High Altitude Pulmonary Edema (HAPE) (West et al 2007), and birth weight reduction (Mortola et al 2000) just above 2000 m.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the evidence to support the relationship between stunting and obesity emerges from some cross-sectional studies that point towards a possible risk of overweight/ obesity among stunted children (7)(8)(9)(10)(11) and adolescents (12)(13)(14) . Some studies have also shown that stunted children and adolescents have higher total body fat percentage (BF%) and central adiposity (14)(15)(16)(17)(18) .…”
mentioning
confidence: 99%